Meningkatkan Hasil Dan Aktivitas Belajar Siswa Muatan Ipa Menggunakan Kombinasi Model PBL CTL, DAN NHT - Muhammad Qastalani Imawan; Tika Puspita Widya Rini (GLOBAL SCIENTS PUBLISHER, 2025)
low activity and learning outcomes of science class V are the problem of research at SDI Rahmatillah Banjarmasin. becaus teacher only uses lecture method without using media or combining models. Through Problem Based Learning model, Contextual Teaching Learning, Numbered Head Together are best alternative solutions. purpose of this study was to describe teacher activities, describe student activities and analyze learning outcomes. This study used qualitative approach with type of Classroom Action Research (CAR). The subjects of the study were fifth grade students a SDI Rahmatillah year 2022/2023, with total of 8 students. Collecting data on teacher and student activities was obtained through observation sheets and student learning outcomes were obtained through individual tests. Data analysis in this study used descriptive analysis techniques translated into tables, graphs, and interpretation with percentages. results of study prove that there is increase in each meeting, namely teacher activity scores 21 with very good criteria, student activities obtain the criteria of